Infant and Young child feeding practices among mothers in Chapagaun VDC. - Basnet, Deepa (2016)
ABSTRACT: A descriptive cross sectional study on "Infant and Young Child Feeding Practices among Mothers in Lalitpur" was carried out for the partial fulfillment of Bachelor of Science in Nursing. The objective of the study was to identify the practice regarding infant and young child feeding (IYCF) among mothers having children 6-23 months. This study was carried out in Chapagaun Primary Health Care and Resource Centre (PHCRC) with sample size 62 by using non probability purposive sampling technique on convenience basis. Interview schedule was used to collect the information. The obtained data was analyzed using descriptive statistics and chi square test was done to find association between dependent and independent variables. Finding of the study revealed that 72.6% initiated breastfeeding within 1 hour of delivery. 72.5% gave colostrums as first feed to the child after delivery and remaining gave infant formula, cow's/buffalo's milk and water. The rate of exclusive breastfeeding was 61.3% while bottle feeding was 35.5%. Very less number of children was initiated complementary feeding at 6 months. Majority 58% mothers practiced complementary feeding after the recommended age and 38.6% before the recommended age. About 24.2% children received dietary diverse meal. Less than half were given marketed complementary food and two third was given food at separate container. Only 12.9% received complementary food with recommended frequency, 40.3% with appropriate consistency and 12.9% with adequate amount. Statistically there was significant association of practice with age of mother as well as mode of delivery. In conclusion practice of breastfeeding was good while complementary feeding practices were poor. The optimal feeding practices were also found to be not appropriate. The findings from the study highlight the importance of education at immunization clinic in order to improve the practices.